Field Extension Worker Information System, Sabang Family Planning Agency - Nurzahri, Muhammad; Ahmad, Lukman (Journal Dekstop Application (JDA), 2022)
This study examines the implementation and evaluation of an information system developed for the data management of Reproductive Health Field Officers (PLKB) at the Community Empowerment, Family Planning, and Women's Empowerment Agency (BPMPKB) in Sabang City. The primary objective was to enhance the efficiency and accuracy of PLKB data administration, thereby facilitating more informed decision-making based on well-documented information. Data collection methods included observation, interviews, and analysis of documentation related to the existing data recording processes. The results indicate that the system's implementation positively influenced the effectiveness and efficiency of PLKB work and improved the quality of the resulting data. Nevertheless, certain challenges require attention, such as the need for more intensive user training and sustained system maintenance